CONVENTIONAL AND CONVERSATIONAL IMPLICATURE IN INSTAGRAM INFLUENCER MARKETING - Sri Widyarti Ali; Nurlaila Husain (Adisam Publisher, 2025)
The rise of social media has significantly changed marketing dynamics, with Instagram influencers now playing a crucial role in shaping consumer perceptions. Despite a growing body of research on social media communication, the specific use of implicature in influencer language remains underexplored. This study addresses this gap by examining how Instagram influencers utilize both conventional and conversational implicature to subtly influence their followers' perceptions and behaviors. The research objective is to analyze the pragmatic strategies employed in influencer posts and assess their impact on follower engagement. A qualitative approach was used, involving a detailed examination of Instagram posts to identify and categorize instances of implicature. The analysis revealed that influencers effectively use conventional implicature, such as phrases like